The Effect of Halal Image, Price, and Promotion on Muslim Consumer Decisions at Muslimah Beauty Clinics - Rahmawati, Zahrah Irma; Zakiy, Muhammad (JURNAL EKONOMI SYARIAH, 2023)
Introduction to The Problem: The growing variety of beauty products makes it profitable for consumers because they have many alternative options to choose from. This makes it necessary for beauty clinics to read consumer desires in order to have loyal customers.Purpose/Objective Study: The purpose of this study was to determine the positive effect of halal image, price and promotion on consumer decisions in choosing a Muslimah beauty clinic.Design/Methodology/Approach: This research is a quantitative research with survey method. The population in this study were female consumers who were in Yogyakarta City and had used Muslimah beauty clinic products and services. The sampling technique used purposive sampling method with a total sample of 200 people.Findings: The results of this study indicate that halal image, price and promotion have a positive effect on consumer decisions in choosing a Muslimah beauty clinic. These results confirm that the element of halalness in beauty products perceived by the Indonesian people is important to fulfill. In addition, with the many diversified beauty products available, companies must pay attention to price and promotion for competitive advantage.Paper Type: Research Article